Influencing Factors and Promotion Strategies for the Adoption or Resistance of Prefabricated Buildings by Construction Companies in Botswana - Otsile Morake; Qingfeng Meng; Agyemang Kwasi Sampene; Francis Kyere (Buildings)
This study investigates the challenges and promotion strategies for adopting Prefabricated Buildings (PFBs) by construction companies in Botswana, using the Behavioral Reasoning Theory (BRT) as the guiding framework. The main research problem addressed is the limited uptake of PFBs within Botswana’s construction industry despite its potential environmental and efficiency benefits. The study aims to understand the reasons for adoption (RFAs) and the reasons against adoption (RAAs) among construction companies. By analyzing responses from 25 participants, the research finds that environmental sustainability, supportive government policies, internal environmental considerations, and time efficiency are key factors driving the adoption of PFB, reflecting a readiness among companies to embrace these technologies. However, significant barriers remain, including industry-specific challenges, technical complexities, transportation issues, and market-related concerns hindering wider adoption. These findings provide actionable insights for policymakers and construction stakeholders to formulate strategies to address these barriers and promote sustainable building practices.